The Synergistic Effect of Nanocrystals Combined With Ultrasound in the Generation of Reactive Oxygen Species for Biomedical Applications - Vighetto, Veronica; Ancona, Andrea; Racca, Luisa; Limongi, Tania; Troia, Adriano; Canavese, Giancarlo; Cauda, Valentina (Frontiers in Bioengineering and Biotechnology, 2019)
Reactive oxygen species (ROS) effects on living cells and tissues is multifaceted and their level or dose can considerably affect cell proliferation and viability. It is therefore necessary understand their role also designing ways able to regulate their amount inside cells, i.e. using engineered nanomaterials with either antioxidant properties or, for cancer therapy applications, capable to induce oxidative stress and cell death, through tunable ROS production. In this paper we report on the use of single-crystalline zinc oxide (ZnO) round-shaped nanoparticles, yet ZnO nanocrystals (NCs) functionalized with amino-propyl groups (ZnO-NH2 NCs), combined with pulsed ultrasound (US). We show the synergistic effects produced by NC-assisted US which are able to produce different amount of ROS, as a result of inertial cavitation under the pulsed US exposure. Using Passive Cavitation Detection (PCD) and Electron Paramagnetic Resonance (EPR) spectroscopy, we systematically study which are the key parameters, monitoring and influencing the amount of generated ROS measuring their concentration in water media and comparing all the results with pure water batches. We thus propose a ROS generation mechanism based on the selective application of US to the ZnO nanocrystals in water solutions. Ultrasound B-mode imaging is also applied, proving in respect to pure water, the enhanced ecographic signal generation of the aqueous solution containing ZnO-NH2 NCs when exposed to pulsed ultrasound. Furthermore, to evaluate the applicability of ZnO-NH2 NCs in the biomedical field, the ROS generation is studied by interposing different tissue mimicking materials, like phantoms and ex vivo tissues, between the US transducer and the sample well. As a whole, we clearly proof the enhanced capability to produce ROS and to control their amount when using ZnO-NH2 NCs in combination with pulsed ultrasound anticipating their applicability in the fields of biology and health care.